The Draft Law on the Indonesian National Armed Forces (TNI) and the Dynamics of Civil-Military Relations: Implications for Democracy and Civilian Supremacy in Indonesia - Hamzah Jamaludin; Nurul Fadhilah (Journal of Politica Governo, 2025)
This research examines the dynamics of civil-military relations in post-Reform Indonesia, with a focus on the latest Draft Law (RUU) on TNI, which has the potential to threaten the principle of civilian supremacy and expand the role of the military in the civilian sphere. Through a qualitative approach and document study method, this research analyzes various provisions in the TNI Bill and compares them with similar regulations in countries that have undergone civil-military relations reform, such as Turkey, Chile and Thailand. The results show that although the bill aims to strengthen the TNI in the face of national threats, some provisions that expand the role of the military risk weakening civilian control and opening up opportunities for the militarization of politics. Therefore, this study recommends strengthening civilian oversight through independent institutions, updating military accountability mechanisms, and revising the TNI Bill to ensure the TNI remains focused on defense functions. The findings contribute to the discourse on civil-military relations in Indonesia and offer a new perspective on the importance of maintaining civilian supremacy in the democratization process.